Resposta :
Resposta:
ESPERO TER AJUDADO!!
Explicação passo-a-passo:
a) 18x – 43 = 65
18x = 65 + 43
18x = 108
x = 108 : 18
x = 6
b) 23x - 16 = 14 - 17x
23 + 17x = 14 + 16
40x = 30
x = 30 : 40
x = 0,75
c) 4.(x + 3) - X = 24 + x
4x + 12 - x = 24 + x
4x - x - x = 24 - 12
2x = 12
x = 12 : 2
x = 6
d) 2x + 28= x + 18
2x - x = 18 - 28
x = -10
e) 10Y - 5.(1 + y) = 3.(2Y - 2) - 20
10y - 5 - 5y = 6x - 6 - 20
10y - 5y - 6y = -6 - 20 + 5
-y = -21 [tex]^{(.1)}[/tex]
y = 21
f) 7.( 2x - 3) + 2.(x + 1) -5.( X - 9) = 3x + 10
14x - 21 + 2x + 2 - 5x - 45 = 3x + 10
14x + 2x - 5x - 3x = 10 + 21 - 2 + 45
8x = 74
x = 74 : 8
x = 9,25
g) 5.( x - 3) - 2x + 3 = 2
5x - 15 - 2x + 3 = 2
5x - 2x = 2 + 15 - 3
3x = 14
x = 14 : 3
x = 4.66666666667